Nickel-copper-nickel corrosion-resistant composite layer and aluminum terminal

By forming a nickel-copper-nickel corrosion-resistant composite layer on the surface of aluminum terminals, the problem of easy oxidation and corrosion of aluminum alloys in power transmission systems is solved, achieving high corrosion resistance in harsh environments, and making it suitable for military, aerospace and automotive fields.

CN116926515BActive Publication Date: 2026-02-03JILIN ZHONG YING HIGH TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310934929.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2026-02-03
Estimated Expiration
2043-07-27

AI Technical Summary

Technical Problem

Aluminum and its alloys are prone to oxidation and corrosion in power transmission systems, leading to increased resistance and connection failure. Existing coating solutions cannot meet the corrosion resistance requirements in harsh environments, which limits their application, especially in the military, aerospace and automotive fields.

Method used

A nickel-copper-nickel corrosion-resistant composite layer, including a first nickel layer, a copper layer, and a second nickel layer, is formed on the surface of the aluminum terminal through electroplating and chemical plating. Combined with a transition layer and a surface layer, the electroplating parameters are optimized to improve density and adhesion.

Benefits of technology

It significantly improves the salt spray corrosion resistance of aluminum terminals, maintaining a protective effect for more than 180 hours in salt spray environments, meeting the requirements for use in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116926515B_ABST
    Figure CN116926515B_ABST
Patent Text Reader

Abstract

The application provides a nickel-copper-nickel corrosion-resistant composite layer and an aluminum terminal. The nickel-copper-nickel corrosion-resistant composite layer comprises a first nickel layer, a copper layer and a second nickel layer; wherein the first nickel layer is a chemical nickel layer, the thickness of the first nickel layer is 1-30 microns; the thickness of the copper layer is 1-15 microns; and the thickness of the second nickel layer is 0.5-30 microns. The application also provides an aluminum terminal provided with the nickel-copper-nickel corrosion-resistant composite layer. The bottom layer of the nickel-copper-nickel corrosion-resistant composite layer has excellent salt spray corrosion resistance, and the aluminum terminal provided with the nickel-copper-nickel corrosion-resistant composite layer can achieve salt spray resistance of more than 180 hours.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to a nickel-copper-nickel corrosion-resistant composite layer and an aluminum terminal and belongs to the technical field of corrosion resistance. BACKGROUND

[0002] Aluminum and its alloys are widely used in the electric energy transmission system of the military industry, automobiles and aerospace industries due to their low density, high electrical conductivity and good forming ability.

[0003] Aluminum and its alloys have the following chemical properties: 1. Aluminum is easily oxidized in the air to form an oxide film layer, which greatly increases the terminal resistance and affects the transmission of electric energy; 2. When aluminum is connected with other metals with more positive standard electrode potential (for example, copper), potential corrosion easily occurs, causing connection failure and even short circuit. The insufficient corrosion resistance of aluminum and its alloys in a corrosive environment restricts the further application of aluminum and its alloys.

[0004] Current electroplating and chemical plating, spraying, laser surface treatment and other processes can protect the substrate by coating a film layer on the surface of aluminum and its alloys, but the effect of the salt spray test is not ideal. The salt spray time of common aluminum workpieces can only be maintained for 48 hours before corrosion occurs, which greatly limits the service life of aluminum workpieces in assemblies.

[0005] Current electroplating manufacturers have less research on aluminum electroplating processes. They only use secondary zinc deposition and nickel plating to make the aluminum workpiece suitable for the next step of electroplating. The selection of the plating layer scheme is not uniform and the effect is general, which makes it difficult to meet the requirements of high corrosion-resistant aluminum workpieces for electroplating, especially aluminum workpieces used in harsh environments such as the military industry, aerospace and automobiles. SUMMARY

[0006] To solve the above technical problems, the purpose of the present application is to provide a corrosion-resistant composite layer based on nickel-copper-nickel, which has excellent corrosion resistance and can meet the corrosion resistance requirements of workpieces in various situations.

[0007] To achieve the above purpose, the present application provides a nickel-copper-nickel corrosion-resistant composite layer, wherein the nickel-copper-nickel corrosion-resistant composite layer comprises a first nickel layer, a copper layer and a second nickel layer.

[0008] The first nickel layer is a chemical nickel layer, and the thickness thereof is 1-30 microns.

[0009] The thickness of the copper layer is 1-15 microns.

[0010] The thickness of the second nickel layer is 5-30 microns.

[0011] According to a specific embodiment of the present application, preferably, the thickness of the first nickel layer is 2-15 microns.

[0012] According to a specific embodiment of the present invention, preferably, the thickness of the copper layer is 5-10 μm.

[0013] According to a specific embodiment of the present invention, preferably, the copper layer is selected from any one of pyrolytic copper, alkali copper, chemical copper, and acid copper.

[0014] According to specific embodiments of the present invention, the copper layers used in the present invention have the following advantages:

[0015] Alkaline copper plating is a cyanide copper plating process. Cyanide has a very strong complexing ability in water, which can greatly increase the cathode polarization of the electroplating process. This causes copper ions to accumulate in large quantities at the cathode and deposit together, increasing the density of the electroplated film. The coating produced by the cyanide system is dense and the reaction is fast and efficient, which can cover the zinc layer with a dense and smooth copper layer. Moreover, copper is chemically inert and has low electroplating internal stress, making it an excellent intermediate coating that is easy to electroplat with subsequent metal coatings.

[0016] The electroplated copper pyrophosphate layer is made of copper pyrophosphate. Pyrophosphate has a stronger complexing ability in water than cyanide, and its cathodic polarization in the pyrophosphate system is also stronger. This is because [Cu(P₂O₇)₂] in the solution... 6- It carries a greater number of negative charges and has a greater impact on the cathode process, while [Cu(P2O7)2] 6- It is difficult to discharge and needs to be hydrolyzed into [CuP2O7]. 2- Only then can a copper layer, [CuP2O7], be deposited via electrical discharge. 2- The hydrolysis is relatively slow, thus further increasing cathodic polarization. The pyroplated copper film is denser with fewer pores, effectively preventing chloride ion penetration in salt spray tests and enhancing the corrosion resistance of the workpiece.

[0017] The chemical copper layer is formed by the orderly deposition of copper ions on a substrate through a chemical reaction autocatalytic plating method. Adding a chemical copper layer between each layer results in good adhesion. The chemical copper layer is an excellent intermediate plating layer that enhances the overall adhesion of the coating. Furthermore, because the preparation process of the chemical copper layer is a purely chemical reaction, it is not affected by current distribution in terms of coating thickness and porosity. Therefore, the chemical copper layer has a more uniform thickness, lower porosity, and good corrosion resistance. Adding this layer in this invention enhances the overall corrosion resistance of the coating.

[0018] The acid copper layer (i.e., acid copper plating) is made by electroplating copper sulfate. It has good adhesion to other plating layers and can serve as an excellent intermediate plating layer. Furthermore, the copper sulfate plating solution used in the preparation of the acid copper layer is stable and low in cost. Adding acid copper between or on both sides of the alkaline copper layer and the pyrolytic copper layer can enhance the overall brightness and corrosion resistance of the plating layer itself.

[0019] According to a specific embodiment of the present invention, preferably, the thickness of the second nickel layer is 10-15 μm.

[0020] According to a specific embodiment of the present invention, preferably, the second nickel layer is selected from any one of nickel aminosulfonate, electroless nickel, and Watt's nickel.

[0021] According to specific embodiments of the present invention, the second nickel layer used in the present invention has the following advantages:

[0022] Nickel sulfamate layers are generally obtained by electroplating. Nickel sulfamate is used as the main salt and nickel chloride is used as the depolarizing agent of the anode. The nickel layer electroplated under this chemical system has good ductility. Compared with other electroplated nickel layers, the film layer electroplated by nickel sulfamate is more tough and has lower internal stress. It can withstand tensile stress without tearing in environments with rapid temperature changes and still maintain its original density. It can effectively protect the workpiece and avoid corrosion in salt spray tests.

[0023] Chemical nickel plating is achieved through electroless nickel plating. Under the action of iron ions as a catalyst, hypophosphatemoids in the solution undergo catalytic dehydrogenation to form active hydrides, which then react with nickel ions in the solution to reduce them, thus chemically depositing nickel onto the workpiece surface to form a chemical nickel layer. The nickel layer deposited by this chemical reaction has a very uniform thickness, and because there is no additional current, it is unaffected by the magnitude of the current or the effect of tip discharge. There is no internal stress between the chemical nickel layer and the workpiece generated by electroplating, truly achieving stress-free plating. In contrast, with conventional electroplating, temperature changes can lead to the release of internal stress between the plating layer and the substrate, making the plating layer more prone to tearing and losing its protective function. Chemical nickel plating, being a chemical deposition process, experiences no internal stress; that is, it only withstands tensile stress during temperature shock tests. Compared to other electroplating processes, it experiences less stress, thus reducing the risk of tearing and allowing it to withstand the effects of temperature shock. Furthermore, it effectively hinders chloride ion penetration and prevents corrosion in salt spray tests. Meanwhile, during the deposition process of electroplating films, hydrogen evolution occurs as a side reaction. The generation and escape of hydrogen leave microscopic pores in the nickel layer, so the amount of hydrogen evolution directly affects the density of the film. Electroless nickel plating, being a purely chemical reaction, does not involve the influence of current density or the overpotential of hydrogen atoms. The hydrogen produced by the side reaction is far less than that of electroplated nickel layers. Therefore, electroless nickel layers have lower porosity, better density, and can more effectively hinder chloride ion penetration, greatly improving the corrosion resistance of the workpiece.

[0024] Watt's nickel layer (i.e. Watt's nickel plating, bright nickel plating) is a nickel sulfate electroplating layer. It has good adhesion to other plating layers and can be used as an excellent intermediate plating layer. When Watt's nickel is added between or on both sides of the alkali copper layer or the pyrocopper layer, a potential difference will be generated in the corrosive environment. It can act as an anode and be corroded first, protecting other plating layers and enhancing the overall brightness and corrosion resistance of the plating layer itself.

[0025] According to a specific embodiment of the present invention, preferably, the nickel-copper-nickel corrosion-resistant composite layer further includes a transition layer, which is disposed on the side of the first nickel layer that is not in contact with the copper layer. This transition layer is disposed between the first nickel layer and the substrate requiring corrosion resistance treatment as a transition, and can be implemented using an appropriate surface treatment method.

[0026] According to a specific embodiment of the present invention, preferably, the transition layer includes a zinc layer, or a combination of a zinc layer and a secondary zinc plating layer; the zinc layer (or zinc layer and secondary zinc plating layer), a first nickel layer, a copper layer, and a second nickel layer are sequentially disposed. The zinc layer and the secondary zinc plating layer serve as transition layers for subsequent electroplating layers, ensuring their adhesion. According to a specific embodiment of the present invention, the combination of the zinc layer and the secondary zinc plating layer includes a configuration where the zinc layer and the secondary zinc plating layer are stacked (layered vertically, with the secondary zinc plating layer covering the zinc layer); and a configuration where the zinc layer and the secondary zinc plating layer are located in different regions of the same layer, and in this configuration, a portion of the two layers may overlap.

[0027] The transition layer of the present invention is not limited to a zinc layer or a secondary zinc plating layer. Other metals or alloys can also be used, as long as they can help improve the adhesion of the corrosion-resistant composite layer. For example, other metal transition layers or alloy transition layers can be formed on the surface of the aluminum terminal by surface treatment processes such as spraying or vacuum electroplating.

[0028] According to a specific embodiment of the present invention, preferably, the thickness of the zinc layer is 0.1-10 μm, more preferably 0.5-1 μm.

[0029] According to a specific embodiment of the present invention, preferably, the thickness of the secondary zinc plating layer is 0.1-10 μm, more preferably 1.5-2.5 μm.

[0030] According to a specific embodiment of the present invention, preferably, the corrosion-resistant composite layer further includes a surface layer.

[0031] According to a specific embodiment of the present invention, preferably, the surface layer is a silver layer or a tin layer to achieve better salt spray effect.

[0032] According to a specific embodiment of the present invention, preferably, the thickness of the surface layer is 2-35 μm, more preferably 3-30 μm, and even more preferably 8-25 μm.

[0033] The nickel-copper-nickel anti-corrosion composite layer provided by this invention can be obtained by sequentially forming a first nickel layer, a copper layer, and a second nickel layer on the surface of a substrate through appropriate methods (electroplating, electroless plating, etc.). When a transition layer is included, the transition layer is formed on the surface of the substrate first, and then the first nickel layer, etc., are formed.

[0034] The present invention also provides an aluminum terminal, wherein a portion or all of the surface of the aluminum terminal is provided with the aforementioned nickel-copper-nickel corrosion-resistant composite layer.

[0035] The method for preparing the aluminum terminal provided by the present invention may include the following steps:

[0036] The front side of the aluminum terminals is rolled and polished.

[0037] The sides of the aluminum terminals are stamped.

[0038] A nickel-copper-nickel corrosion-resistant composite layer is formed sequentially on the front and side of the treated aluminum terminal (through electroplating, chemical plating, etc.) to obtain an aluminum terminal with a nickel-copper-nickel corrosion-resistant composite layer.

[0039] In the above-mentioned methods for preparing aluminum terminals, rolling, polishing, and stamping processes can be performed only on the areas requiring corrosion resistance treatment, and are not limited to the entire surface of the aluminum terminal. By employing localized treatment, welding is facilitated, allowing for the application of various joining processes such as friction welding, friction stir welding, ultrasonic welding, molecular diffusion welding, and resistance welding, thereby obtaining corrosion-resistant terminals with high reliability and multiple joining capabilities.

[0040] In the above-mentioned method for preparing aluminum terminals, preferably, by performing a roll forming process on the terminal material, the density of the terminal surface can be enhanced, thereby improving the corrosion resistance of the subsequent electroplating process.

[0041] In the above-described method for preparing aluminum terminals, preferably, polishing the terminal material enhances the surface smoothness of the terminal and improves the corrosion resistance of subsequent electroplating. Polishing can be performed using methods such as chemical polishing or mechanical polishing.

[0042] In the above-mentioned method for preparing aluminum terminals, preferably, the surface roughness of the aluminum terminal after roll forming and polishing is less than Ra 3.6, more preferably less than Ra 0.8, that is, the surface roughness of the aluminum substrate used to prepare the aluminum terminal is less than Ra 3.6, more preferably less than Ra 0.8.

[0043] In the above-mentioned method for preparing aluminum terminals, preferably, the side roughness of the aluminum terminal after roll forming is less than Ra 3.6 (more preferably less than Ra 0.8), and the bright band is greater than 50% (more preferably greater than 98%). That is, the side roughness of the aluminum substrate used to prepare the aluminum terminal is less than Ra 3.6 (more preferably less than Ra 0.8), and the bright band is greater than 50% (preferably greater than 98%).

[0044] In the above-described method for preparing aluminum terminals, preferably, when a transition layer is provided, a transition layer is first formed on the front and side surfaces of the treated aluminum terminal before the first nickel layer is formed.

[0045] The bottom layer of the nickel-copper-nickel corrosion-resistant composite layer provided by the present invention has excellent salt spray corrosion resistance, and the aluminum terminals equipped with the nickel-copper-nickel corrosion-resistant composite layer can achieve salt spray resistance for more than 180 hours. Attached Figure Description

[0046] Figure 1 This is an exemplary overall structural diagram of an aluminum terminal with a nickel-copper-nickel corrosion-resistant composite layer provided by the present invention.

[0047] Figure 2 This is a schematic diagram of an exemplary electroplating process for an aluminum terminal with a nickel-copper-nickel corrosion-resistant composite layer provided by the present invention.

[0048] Figure 3 This is a diagram showing the condition of the sample after a 228-hour corrosion resistance test.

[0049] Figure 4 This is a diagram showing the condition of the sample after a 120-hour corrosion resistance test.

[0050] Figure 5 This is a diagram showing the condition of the sample after a 180-hour corrosion resistance test. Detailed Implementation

[0051] In order to provide a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention will now be described in detail below, but it should not be construed as limiting the scope of implementation of the present invention.

[0052] A typical structure of the aluminum terminal with a nickel-copper-nickel corrosion-resistant composite layer provided by the present invention is as follows: Figure 1 As shown. The aluminum terminal includes an aluminum substrate 1 and a nickel-copper-nickel corrosion-resistant composite layer disposed on the surface of the aluminum substrate 1;

[0053] The nickel-copper-nickel corrosion-resistant composite layer includes a transition layer 2, a first nickel layer 3, a copper layer 4, a second nickel layer 5, and a surface layer 6, wherein:

[0054] The transition layer 2 can be a zinc layer or a combination of a zinc layer and a secondary zinc plating layer;

[0055] The first nickel layer 3 is selected from chemical nickel layers;

[0056] Copper layer 4 is selected from any one of pyrolytic copper, alkali copper, chemical copper, and acid copper;

[0057] The second nickel layer 5 is selected from any one of nickel aminosulfonate, electroless nickel, and Watt nickel;

[0058] Surface layer 6 is selected from silver or tin.

[0059] The electroplating process of the aluminum terminals of the present invention may include the following steps: ultrasonic degreasing, alkaline washing, acid washing, activation, electroless nickel plating (first nickel layer), electroplating copper or electroless copper plating, electroplating nickel or electroless nickel plating, electroplating surface layer, post-treatment, pure water washing, and drying.

[0060] When a transition layer is provided, chemical zinc precipitation, chemical zinc stripping, and secondary zinc precipitation can be performed after activation. The secondary zinc precipitation step can be selected as needed.

[0061] An exemplary electroplating process for the aluminum terminals of the present invention is as follows: Figure 2 As shown.

[0062] The technical solution of the present invention starts with the design to avoid contact between chloride ions and the substrate. The front side of the material terminal is subjected to roll forming and polishing treatment, and the roughness after treatment is less than Ra 3.6, preferably less than Ra 0.8. The side of the material terminal is processed by precision stamping process, and the bright band after treatment is greater than 50%, preferably greater than 98%, and the roughness is less than Ra 3.6, preferably less than Ra 0.8.

[0063] The roll forming process involves repeatedly rolling an aluminum plate sandwiched between two rollers. This mechanical pressure increases the surface density of the aluminum material, thereby reducing the porosity of the aluminum terminal material and improving its compactness. This prepares the material for the subsequent electroplating layer; fewer pores in the material result in a less porous electroplated film with higher protective properties. Roll forming also reduces the surface roughness of the aluminum plate and significantly improves its flatness.

[0064] The polishing process involves placing the terminal material in a polishing tank containing a polishing solution and magnetic needles. Magnetic polishing uses an electric current to generate a magnetic field, which drives stainless steel needles (i.e., magnetic needles) to move. During this movement, the magnetic needles rub against the surface of the terminal material, thereby achieving a mechanical polishing effect and improving the smoothness and flatness of the terminal material surface.

[0065] Polishing and precision stamping processes are all used to improve the smoothness and flatness of the front and sides of the terminal material.

[0066] Improving the flatness and smoothness of the terminal material greatly benefits the electroplating film layer. Because of the influence of current, the electroplating process accumulates more film in areas where electrons are concentrated on the workpiece. This results in uneven film thickness on the terminal surface, and even numerous pits, allowing chloride ions in the salt spray to accumulate and penetrate. When the flatness of the terminal material is insufficient, due to the principle of point discharge, the more curved the conductor surface, the more charge accumulates in areas with a relatively small surface area. Uneven protrusions on the material surface will accumulate a large number of electrons, making the protrusions on the electroplated workpiece surface even more prominent, and the depressions even more recessed. This forms pinholes, which easily accumulate salt spray solution, causing chloride ions to penetrate and leading to corrosion. After processing with the process of this invention, the terminal material can be effectively covered with an electroplating film layer, effectively improving its corrosion resistance.

[0067] Electroplating of alkaline copper: Electroplating parameters are as follows: cuprous cyanide: 40-50 g / L, total sodium cyanide: 40-60 g / L, free sodium cyanide: 8-14 g / L, potassium sodium tartrate: 30-45 g / L, sodium hydroxide: 1-3 g / L, additives (one or more of polyethylene glycol, fatty amine polyoxyethylene ether (AEO), and OP series octylphenol polyoxyethylene ether): 3-5 mL / L, temperature: 40-50℃, anode-cathode area ratio: 1:1.5, current density: 0.7-1.2 A / dm², electroplating time: 5-15 min, and coating thickness is selected as needed.

[0068] To enhance the density of the coating, this invention optimizes the process: Generally, to meet electroplating efficiency requirements and achieve faster production, electroplating plants use a current density of 4-10 A / dm² for alkaline copper plating, which is significantly higher than that of this invention. Current density directly affects the density of the coating; high current density weakens cathodic polarization and makes it easier to reach the hydrogen ion evolution overpotential in the solution, causing hydrogen evolution side reactions during electroplating. The evolved hydrogen gas leaves pores in the coating, reducing its density. The alkaline copper plating process used in this invention reduces the current density while increasing the concentration of the main salt, cuprous cyanide, and free sodium cyanide, thereby obtaining an alkaline copper coating with excellent electroplating efficiency and density.

[0069] Electroplating of copper pyrophosphate: Electroplating parameters are as follows: copper pyrophosphate: 50-70 g / L, potassium pyrophosphate: 300-450 g / L, ammonium citrate: 15-30 g / L, ammonia: 2-5 mL / L, current density: 0.7-1.2 A / dm³ 2 The temperature is 40-50℃, the anode-cathode area ratio is 1:1.5, the electroplating time is 50-90 min, and the coating thickness is controlled by adjusting the electroplating parameters as needed.

[0070] The parameters for electroless copper plating are as follows: Composition of the electroless plating solution: copper sulfate: 5-20 g / L, sodium hypophosphite: 20-50 g / L, sodium citrate: 5-30 g / L, nickel sulfate: 0.1-5 g / L, potassium ferrocyanide: 0.5-7 mg / L, boric acid: 15-50 g / L; temperature: 60-90℃, pH: 7.8-10.2, plating time: 40-100 min, typical plating rate: 1 μm / 6 min, i.e., 6 min-1 μm, 24 min-4 μm, 48 min-8 μm; the plating thickness can be controlled as needed by adjusting the electroless copper plating parameters.

[0071] The parameters for electroplating acid copper are as follows: Electroplating solution composition: Copper sulfate pentahydrate: 160-250 g / L, sulfuric acid: 25-50 mL / L, chloride ions: 40-120 ppm, additives (sodium polydithiopropane sulfonate, 2-mercaptobenzimidazole, 1,2-ethylidene thiourea, or a mixture of one or more polyamine compounds): 4-15 mL / L, current density: 0.8-2.0 A / dm³ 2 The temperature is 20-30℃, the anode-cathode area ratio is 1:1.5, the electroplating time is 20-80 min, and the coating thickness is controlled by adjusting the electroplating parameters as needed.

[0072] Electroless nickel plating layer: The electroless nickel plating parameters are as follows: Based on the total volume of the electroless plating solution, the electroless nickel plating solution used for the layer contains nickel sulfate: 15-25 g / L, sodium hypophosphite: 15-25 g / L, sodium acetate: 20-30 g / L, succinic acid: 5-10 g / L, and lactic acid: 10-20 g / L; the remaining component in the plating solution is water. The electroless nickel plating temperature is 85-95℃, and the electroless plating time is 20-40 min. The electroless nickel plating reaction rate is stable. Following the method of this invention, the typical nickel plating rate is 1 μm / 5 min, i.e., 5 min - 1 μm, 20 min - 4 μm, and 40 min - 8 μm.

[0073] Nickel sulfamate layer: Electroplating parameters are as follows: Electroplating solution composition: Nickel sulfamate: 300-500g / L, Nickel chloride: 10-25g / L, Boric acid: 30-40g / L, Sulfamic acid: 100-150g / L, Additives: 5-10ml / L, Current density: 0.8-1.2A / dm², Temperature: 50-60℃, Anode-cathode area ratio: 1:1.5, Electroplating time: 1-80min (preferably 40-60min), and the coating thickness is controlled as needed by controlling the electroplating parameters.

[0074] The parameters for electroplating Watt's nickel layer are as follows: Electroplating solution composition: Nickel sulfate hexahydrate: 250-350 g / L, Nickel chloride hexahydrate: 60-95 g / L, Boric acid: 40-60 g / L, Additives (sodium dodecyl sulfate, saccharin, butynediol ethoxylate, or one or more of these): 6-12 mL / L, pH 3-5, Current density 0.8-2.0 A / dm³ 2 The temperature is 50-60℃, the anode-cathode area ratio is 1:1.5, the electroplating time is 30-70 min, and the coating thickness is controlled by adjusting the electroplating parameters as needed.

[0075] The surface electroplating can be performed using conventional methods in the field, for example:

[0076] The electroplating parameters for silver are as follows: Electroplating solution composition: silver cyanide: 30-50 g / L, potassium cyanide: 130-150 g / L, free potassium cyanide: 45-60 g / L, potassium carbonate: 15-25 g / L, potassium hydroxide: 4-10 g / L, additives (one or more of thiocarbamate, sodium dodecyl sulfonate, and OP series octylphenol polyoxyethylene ether): 20-30 g / L, temperature: 20-25℃, anode-cathode area ratio: 1:1.5, current density: 0.2-0.5 A / dm², electroplating time: 30-60 min, and the coating thickness is controlled as needed by adjusting the electroplating parameters.

[0077] The electroplating parameters for tin are as follows: Electroplating solution composition: stannous sulfate: 10-50 g / L, sulfuric acid: 60-190 ml / L, gelatin: 1-10 g / L, formaldehyde: 5-10 ml / L, benzyl acetone: 5-30 g / L; Temperature: 10-40℃, anode-cathode area ratio: 1:1.5, current density: 0.7-1.2 A / dm², electroplating time: 30-120 min, and the coating thickness can be controlled as needed by adjusting the electroplating parameters.

[0078] Salt spray corrosion resistance tests in all embodiments and comparative examples were conducted in accordance with the national standard GB / T 2423.17-2008. Acceptance criteria: No corrosion was observed in the coating, no surface pitting, peeling, blistering, etc., and the coating showed no spots or color changes.

[0079] Example 1

[0080] This embodiment provides an aluminum terminal with a nickel-copper-nickel corrosion-resistant composite layer, wherein:

[0081] The front side of the aluminum terminal material has undergone roll forming and polishing, with a roughness of less than Ra 0.8. The side side has undergone precision stamping, with a bright band greater than 98% and a roughness of less than Ra 0.8. The roughness of the surface and side of the aluminum terminal material before and after polishing is 0.168μm, respectively. It can be seen that polishing can significantly reduce surface roughness and improve smoothness. In the roughness test, the sampling cutoff wavelength of the filter is λc=0.8mm×5.

[0082] The nickel-copper-nickel corrosion-resistant composite layer includes a primary zinc plating layer (1μm thick), a secondary zinc plating layer (2μm thick), a chemical nickel plating layer (10μm thick), a pyrometallurgical copper plating layer (10μm thick), and a nickel sulfamate plating layer (15μm thick).

[0083] The aluminum terminal was subjected to a salt spray resistance test, and the salt spray resistance time was measured to be 228 hours.

[0084] The test results above show that the corrosion-resistant composite layer provided in this embodiment has excellent salt spray corrosion resistance.

[0085] Example 2

[0086] This embodiment provides an aluminum terminal with a nickel-copper-nickel corrosion-resistant composite layer, wherein:

[0087] The front side of the aluminum terminal material has been rolled and polished, with a roughness of less than Ra 0.8. The side side has been processed by precision stamping, with a bright band of more than 98% and a roughness of less than Ra 0.8.

[0088] The nickel-copper-nickel corrosion-resistant composite layer includes a primary zinc plating layer (1μm thick), a secondary zinc plating layer (2μm thick), a chemical nickel plating layer (5μm thick), an acid copper plating layer (8μm thick), and a chemical nickel plating layer (12μm thick).

[0089] The aluminum terminal was subjected to a salt spray resistance test, and the salt spray resistance time was measured to be 180 hours.

[0090] The test results above show that the corrosion-resistant composite layer provided in this embodiment has excellent salt spray corrosion resistance.

[0091] The morphology of the aluminum terminals in Examples 1 and 2 after a 228-hour salt spray test is as follows. Figure 3 As shown, the left side is the sample from Example 1, and the right side is the sample from Example 2. Figure 3 It can be seen that the test piece of Example 1 did not undergo significant changes, while the surface of the test piece of Example 2 showed some changes. Although they were not very obvious, they were still noticeable compared to Example 1. Therefore, the salt spray resistance of the nickel-copper-nickel corrosion-resistant composite layer of Example 1 was better than that of Example 2.

[0092] Comparative Example 1

[0093] This comparative example provides an aluminum terminal with a corrosion-resistant composite layer, wherein:

[0094] The front side of the aluminum terminal material has been rolled and polished, with a roughness of less than Ra 0.8. The side side has been processed by precision stamping, with a bright band of more than 98% and a roughness of less than Ra 0.8.

[0095] The corrosion-resistant composite layer includes a primary zinc plating layer (1 μm thick), a secondary zinc plating layer (2 μm thick), a copper plating layer (20 μm thick), and a nickel sulfamate layer (15 μm thick).

[0096] The aluminum terminal was subjected to a salt spray resistance test, and the salt spray resistance time was measured to be 120 hours.

[0097] The morphology of the aluminum terminals of Example 1 and Comparative Example 1 after a 120-hour salt spray test is as follows. Figure 4 As shown, the left side is the sample from Example 1, and the right side is the sample from Comparative Example 1. Figure 4 It can be seen that the test piece in Example 1 did not undergo significant changes, while the test piece in Comparative Example 1 showed problems such as blistering on its surface, indicating that the salt spray had penetrated the corrosion-resistant layer on the surface of the test piece and contacted the test piece substrate, thus corroding the test piece substrate.

[0098] The test results above show that the corrosion-resistant composite layer provided in this comparative example has relatively poor salt spray corrosion resistance.

[0099] Comparative Example 2

[0100] This comparative example provides an aluminum terminal with a corrosion-resistant composite layer, wherein:

[0101] The front side of the aluminum terminal material has been rolled and polished, with a roughness of less than Ra 0.8. The side side has been processed by precision stamping, with a bright band of more than 98% and a roughness of less than Ra 0.8.

[0102] The corrosion-resistant composite layer includes a primary zinc plating layer (1 μm thick), a secondary zinc plating layer (2 μm thick), a chemical nickel plating layer (20 μm thick), and a nickel sulfamate layer (15 μm thick).

[0103] The aluminum terminal was subjected to a salt spray resistance test, and the salt spray resistance time was measured to be 108 hours.

[0104] The test results above show that the corrosion-resistant composite layer provided in this comparative example has relatively poor salt spray corrosion resistance.

[0105] Comparative Example 3

[0106] This comparative example provides an aluminum terminal with a corrosion-resistant composite layer, wherein:

[0107] The front side of the aluminum terminal material has been rolled and polished, with a roughness of less than Ra 0.8. The side side has been processed by precision stamping, with a bright band of more than 98% and a roughness of less than Ra 0.8.

[0108] The corrosion-resistant composite layer consists of a primary zinc plating layer (1 μm thick), a secondary zinc plating layer (2 μm thick), and a chemical nickel plating layer (25 μm thick).

[0109] The aluminum terminal was subjected to a salt spray resistance test, and the salt spray resistance time was measured to be 96 hours.

[0110] The morphology of the aluminum terminals in Example 2 and Comparative Example 3 after a 120-hour salt spray test is as follows. Figure 5 As shown, the left side is the sample from Example 2, and the right side is the sample from Comparative Example 3. Figure 5 It can be seen that the test piece in Example 2 did not undergo significant changes, while the test piece in Comparative Example 3 showed problems such as blistering and fading, indicating that the salt spray had penetrated the corrosion-resistant layer on the surface of the test piece and contacted the test piece substrate, thus corroding the test piece substrate.

[0111] The test results above show that the corrosion-resistant composite layer provided in this comparative example has relatively poor salt spray corrosion resistance.

[0112] Comparative Example 4

[0113] This comparative example provides an aluminum terminal with a corrosion-resistant composite layer, wherein:

[0114] The front side of the aluminum terminal material has been rolled and polished, with a roughness of less than Ra 0.8. The side side has been processed by precision stamping, with a bright band of more than 98% and a roughness of less than Ra 0.8.

[0115] The corrosion-resistant composite layer includes a primary zinc plating layer (1 μm thick), a secondary zinc plating layer (2 μm thick), an acid copper layer (13 μm), and a chemical nickel plating layer (12 μm thick).

[0116] The aluminum terminal was subjected to a salt spray resistance test, and the salt spray resistance time was measured to be 48 hours.

[0117] The test results above show that the corrosion-resistant composite layer provided in this comparative example has relatively poor salt spray corrosion resistance.

[0118] Example 3

[0119] This embodiment provides an aluminum terminal with a nickel-copper-nickel corrosion-resistant composite layer, wherein:

[0120] The front side of the aluminum terminal material has been rolled and polished, with a roughness of less than Ra 0.8. The side side has been processed by precision stamping, with a bright band of more than 98% and a roughness of less than Ra 0.8.

[0121] The nickel-copper-nickel corrosion-resistant composite layer includes a primary zinc plating layer (1μm thick), a secondary zinc plating layer (2μm thick), a chemical nickel plating layer (10μm thick), a pyrometallurgical copper plating layer (10μm thick), a nickel sulfamate plating layer (15μm thick), and a tin plating layer (15μm thick).

[0122] The aluminum terminal was subjected to a salt spray resistance test, and the salt spray resistance time was measured to be 336 hours.

[0123] The test results above show that the corrosion-resistant composite layer provided in this embodiment has excellent salt spray corrosion resistance. Compared with Example 1, the salt spray resistance time is increased by 47% when a tin layer is added as the surface layer.

[0124] Example 4

[0125] This embodiment provides an aluminum terminal with a nickel-copper-nickel corrosion-resistant composite layer, wherein:

[0126] The front side of the aluminum terminal material has been rolled and polished, with a roughness of less than Ra 0.8. The side side has been processed by precision stamping, with a bright band of more than 98% and a roughness of less than Ra 0.8.

[0127] The nickel-copper-nickel corrosion-resistant composite layer includes a primary zinc plating layer (1 μm thick), a secondary zinc plating layer (2 μm thick), a chemical nickel plating layer (1 μm thick), an alkali copper plating layer (1 μm thick), and a nickel sulfamate plating layer (0.5 μm thick).

[0128] The aluminum terminal was subjected to a salt spray resistance test, and the salt spray resistance time was measured to be 52 hours.

[0129] The test results above show that the corrosion-resistant composite layer provided in this embodiment has excellent salt spray corrosion resistance and is suitable for the welding area of ​​aluminum terminals or areas that are not directly exposed.

[0130] Comparative Example 5

[0131] This comparative example provides an aluminum terminal with a nickel-copper-nickel corrosion-resistant composite layer, wherein:

[0132] The front side of the aluminum terminal material has been rolled and polished, with a roughness of less than Ra 0.8. The side side has been processed by precision stamping, with a bright band of more than 98% and a roughness of less than Ra 0.8.

[0133] The nickel-copper-nickel corrosion-resistant composite layer includes a primary zinc plating layer (1 μm thick), a secondary zinc plating layer (2 μm thick), a chemical nickel plating layer (0.2 μm thick), an alkali copper plating layer (1 μm thick), and a nickel sulfamate plating layer (0.5 μm thick).

[0134] The aluminum terminal was subjected to a salt spray resistance test, and the salt spray resistance time was measured to be 36 hours.

[0135] The test results above show that the thickness of the corrosion-resistant composite layer provided in this comparative example is relatively low, and its salt spray corrosion resistance cannot reach 48H, which is lower than that of conventional coatings.

[0136] Comparative Example 6

[0137] This comparative example provides an aluminum terminal with a nickel-copper-nickel corrosion-resistant composite layer, wherein:

[0138] The front side of the aluminum terminal material has been rolled and polished, with a roughness of less than Ra 0.8. The side side has been processed by precision stamping, with a bright band of more than 98% and a roughness of less than Ra 0.8.

[0139] The nickel-copper-nickel corrosion-resistant composite layer includes a primary zinc plating layer (1 μm thick), a secondary zinc plating layer (2 μm thick), a chemical nickel plating layer (1 μm thick), an alkali copper plating layer (0.2 μm thick), and a nickel sulfamate plating layer (0.5 μm thick).

[0140] The aluminum terminal was subjected to a salt spray resistance test, and the salt spray resistance time was measured to be 40 hours.

[0141] The test results above show that the thickness of the corrosion-resistant composite layer provided in this comparative example is relatively low, and its salt spray corrosion resistance cannot reach 48H, which is lower than that of conventional coatings.

[0142] Comparative Example 7

[0143] This comparative example provides an aluminum terminal with a nickel-copper-nickel corrosion-resistant composite layer, wherein:

[0144] The front side of the aluminum terminal material has been rolled and polished, with a roughness of less than Ra 0.8. The side side has been processed by precision stamping, with a bright band of more than 98% and a roughness of less than Ra 0.8.

[0145] The nickel-copper-nickel corrosion-resistant composite layer includes a primary zinc plating layer (1 μm thick), a secondary zinc plating layer (2 μm thick), a chemical nickel plating layer (1 μm thick), an alkali copper plating layer (1 μm thick), and a nickel sulfamate plating layer (0.1 μm thick).

[0146] The aluminum terminal was subjected to a salt spray resistance test, and the salt spray resistance time was measured to be 24 hours.

[0147] The test results above show that the thickness of the corrosion-resistant composite layer provided in this comparative example is relatively low, and its salt spray corrosion resistance cannot reach 48H, which is lower than that of conventional coatings.

[0148] Example 5

[0149] This embodiment provides an aluminum terminal with a nickel-copper-nickel corrosion-resistant composite layer, wherein:

[0150] The front side of the aluminum terminal material has been rolled and polished, with a roughness of less than Ra 0.8. The side side has been processed by precision stamping, with a bright band of more than 98% and a roughness of less than Ra 0.8.

[0151] The nickel-copper-nickel corrosion-resistant composite layer includes a primary zinc plating layer (1 μm thick), a secondary zinc plating layer (2 μm thick), a chemical nickel plating layer (1 μm thick), an alkaline copper plating layer (1 μm thick), and a chemical nickel plating layer (0.5 μm thick).

[0152] The aluminum terminal was subjected to a salt spray resistance test, and the salt spray resistance time was measured to be 50 hours.

[0153] The test results above show that the corrosion-resistant composite layer provided in this embodiment has excellent salt spray corrosion resistance and is suitable for the welding area of ​​aluminum terminals or areas that are not directly exposed.

[0154] Comparative Example 8

[0155] This comparative example provides an aluminum terminal with a nickel-copper-nickel corrosion-resistant composite layer, wherein:

[0156] The front side of the aluminum terminal material has been rolled and polished, with a roughness of less than Ra 0.8. The side side has been processed by precision stamping, with a bright band of more than 98% and a roughness of less than Ra 0.8.

[0157] The nickel-copper-nickel corrosion-resistant composite layer includes a primary zinc plating layer (1 μm thick), a secondary zinc plating layer (2 μm thick), a chemical nickel plating layer (0.2 μm thick), an alkaline copper plating layer (1 μm thick), and a chemical nickel plating layer (0.5 μm thick).

[0158] The aluminum terminal was subjected to a salt spray resistance test, and the salt spray resistance time was measured to be 36 hours.

[0159] The test results above show that the thickness of the corrosion-resistant composite layer provided in this comparative example is relatively low, and its salt spray corrosion resistance cannot reach 48H, which is lower than that of conventional coatings.

[0160] Comparative Example 9

[0161] This comparative example provides an aluminum terminal with a nickel-copper-nickel corrosion-resistant composite layer, wherein:

[0162] The front side of the aluminum terminal material has been rolled and polished, with a roughness of less than Ra 0.8. The side side has been processed by precision stamping, with a bright band of more than 98% and a roughness of less than Ra 0.8.

[0163] The nickel-copper-nickel corrosion-resistant composite layer includes a primary zinc plating layer (1 μm thick), a secondary zinc plating layer (2 μm thick), a chemical nickel plating layer (1 μm thick), an alkaline copper plating layer (0.2 μm thick), and a chemical nickel plating layer (0.5 μm thick).

[0164] The aluminum terminal was subjected to a salt spray resistance test, and the salt spray resistance time was measured to be 38 hours.

[0165] The test results above show that the thickness of the corrosion-resistant composite layer provided in this comparative example is relatively low, and its salt spray corrosion resistance cannot reach 48H, which is lower than that of conventional coatings.

[0166] Comparative Example 10

[0167] This comparative example provides an aluminum terminal with a nickel-copper-nickel corrosion-resistant composite layer, wherein:

[0168] The front side of the aluminum terminal material has been rolled and polished, with a roughness of less than Ra 0.8. The side side has been processed by precision stamping, with a bright band of more than 98% and a roughness of less than Ra 0.8.

[0169] The nickel-copper-nickel corrosion-resistant composite layer includes a primary zinc plating layer (1 μm thick), a secondary zinc plating layer (2 μm thick), a chemical nickel plating layer (1 μm thick), an alkaline copper plating layer (1 μm thick), and a chemical nickel plating layer (0.1 μm thick).

[0170] The aluminum terminal was subjected to a salt spray resistance test, and the salt spray resistance time was measured to be 24 hours.

[0171] The test results above show that the thickness of the corrosion-resistant composite layer provided in this comparative example is relatively low, and its salt spray corrosion resistance cannot reach 48H, which is lower than that of conventional coatings.

[0172] Example 6

[0173] This embodiment provides an aluminum terminal with a nickel-copper-nickel corrosion-resistant composite layer, wherein:

[0174] The front side of the aluminum terminal material has been rolled and polished, with a roughness of less than Ra 0.8. The side side has been processed by precision stamping, with a bright band of more than 98% and a roughness of less than Ra 0.8.

[0175] The nickel-copper-nickel corrosion-resistant composite layer includes a primary zinc plating layer (1 μm thick), a secondary zinc plating layer (2 μm thick), a chemical nickel plating layer (20 μm thick), a pyrometallurgical copper plating layer (10 μm thick), and a nickel sulfamate plating layer (20 μm thick).

[0176] The aluminum terminal was subjected to a salt spray resistance test, and the salt spray resistance time was measured to be 224 hours.

[0177] The test results above show that the corrosion-resistant composite layer provided in this embodiment has a high thickness and excellent salt spray corrosion resistance.

Claims

1. A nickel-copper-nickel corrosion-resistant composite layer, characterized in that, The nickel-copper-nickel corrosion-resistant composite layer is composed of a transition layer, a first nickel layer, a copper layer and a second nickel layer arranged in sequence, or it is composed of a transition layer, a first nickel layer, a copper layer, a second nickel layer and a surface layer arranged in sequence. The transition layer includes a primary zinc plating layer and a secondary zinc plating layer, wherein the thickness of the primary zinc plating layer is 0.1-10 μm and the thickness of the secondary zinc plating layer is 0.1-10 μm. The first nickel layer is a chemical nickel layer with a thickness of 1-30 μm; The thickness of the copper layer is 1-15 μm, and the copper layer is selected from any one of pyrolytic copper, alkali copper, chemical copper, and acid copper. The thickness of the second nickel layer is 0.5-30 μm, and the second nickel layer is selected from any one of nickel sulfamate, electroless nickel, and Watt's nickel; The surface layer is a silver layer or a tin layer; the thickness of the surface layer is 2-35 μm.

2. The nickel-copper-nickel corrosion-resistant composite layer according to claim 1, characterized in that, The thickness of the first nickel layer is 2-15 μm.

3. The nickel-copper-nickel corrosion-resistant composite layer according to claim 1, characterized in that, The thickness of the copper layer is 5-10 μm.

4. The nickel-copper-nickel corrosion-resistant composite layer according to claim 1, characterized in that, The thickness of the second nickel layer is 10-15 μm.

5. The nickel-copper-nickel corrosion-resistant composite layer according to claim 1, characterized in that, The thickness of the primary zinc plating layer is 0.5-1 μm.

6. The nickel-copper-nickel corrosion-resistant composite layer according to claim 1, characterized in that, The thickness of the secondary zinc plating layer is 1.5-2.5 μm.

7. The nickel-copper-nickel corrosion-resistant composite layer according to claim 1, characterized in that, The thickness of the surface layer is 8-25 μm.

8. An aluminum terminal, characterized in that, The aluminum terminal has a portion or all of its surface covered with a nickel-copper-nickel corrosion-resistant composite layer as described in any one of claims 1-7.

9. The aluminum terminal according to claim 8, characterized in that, The surface roughness of the aluminum substrate used to prepare the aluminum terminal is less than Ra 3.

6.

10. The aluminum terminal according to claim 9, characterized in that, The surface roughness of the aluminum substrate used to prepare the aluminum terminal is less than Ra 0.

8.

11. The aluminum terminal according to claim 9, characterized in that, The aluminum substrate used to prepare the aluminum terminal has a side roughness of less than Ra 3.6 and a bright band of more than 50%.

12. The aluminum terminal according to claim 11, characterized in that, The surface roughness of the aluminum substrate used to prepare the aluminum terminal is less than Ra 0.

8.

13. The aluminum terminal according to claim 11, characterized in that, The aluminum substrate used to prepare this aluminum terminal has a bright band on its side that is greater than 98%.

Citation Information

Patent Citations

  • Environment-friendly gold-plated coating structure of aluminum alloy die casting

    CN212103011U